Pengaruh Bermain Bowling terhadap Perkembangan Motorik anak Kelompok A di TK PERTIWI II Donohudan Ngemplak Boyolali Tahun Ajaran 2015/2016 - Putri Hari Sekti, Ninda; , Drs. Haryono Yuwono (2016)
This research is motivated by the children's gross motor development which still vary. This is because the learning activities to develop gross motor less varied and playing bowling has never been done. The purpose of this study was to determine the effect of playing bowling on children,s motor development group A KindergartenPertiwi II Donohudan. This study was an experimental study. The experimental desain used is pre-experimental design with one pretest-poesttest design. The subjects in this study were children in group A amounting 16 children. The data collection technique of gross motor development used is observation. The data were analyzed using t-tes. The results of children,s gross motor development in group A obtained an average score of 11.1250 on the prtest and an average score of 15.375on the posttest. The results of t-test data analysis obtained that t count -14.368 ≤ -t table=1.753. This shows that Ha is accepted and Ho is rejected. The conclusion of this study is that playing bowling affects on the gross motor development of children in group A Kindergarten Pertiwi II DonohudanNgemplakBoyolaliAcademic Year 2015/ 2016.